219k views
5 votes
Please help me with this !!!!!!!

Please help me with this !!!!!!!-example-1
User Graymatter
by
5.5k points

1 Answer

3 votes

Answer:

y = 2x - 1

Explanation:

Note the difference between consecutive terms of y are constant, that is

1 - (- 1) = 3 - 1 = 5 - 3 = 7 - 5 = 9 - 7 = 2

Thus the equation is of the form y = 2x ± c ← c is a constant

Substitute values of x to determine the required value of c

x = 0 : 2 × 0 = 0 ← require to subtract 1 for y = - 1

x = 1 : 2 × 1 = 2 ← require to subtract 1 for y = 1

x = 2 : 2 × 2 = 4 ← require to subtract 1 for y = 3, and so on

Thus the required equation is

y = 2x - 1

User Joffrey Outtier
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.